The Effect of Self-Care on the Severity of Disability of Leprosy Patients in the Work Area Galis Health Center - Mufarika; Nicky Citra Auliya; Merina Widyastuti (Universitas STRADA Indonesia, 2022)
Background: People with leprosy tend to have dry skin due to damage. Purpose: This study aims to analyze differences in the severity of disability in patients before and after self-care in the treatment group and the control group. Methods: This research used a Quasy experiment pretest posttest with a control group design. The population was 52 respondents, with a sample of 34 respondents. The sampling technique used purposive sampling. Results: The results of the study using the Wilcoxon test showed that there was a difference in the severity of disability in the treatment group with a p-value of 0,00 < 0.05 and no difference in the severity of disability in the control group with a p-value of 0,105 > 0.05. Based on the results of the Mann-Whitney test, it was found that there were differences in the severity of disability in the treatment group and the control group before and after self-care with a p-value of 0,00 < 0,05. Conclusion: The researcher suggests that sufferers can continue to improve efforts to prevent the severity of leprosy disability by taking regular self-care.